Metatheatricality and Self-reflexivity in Subedi’s Plays - Shrivastwa, Bimal Kishore (KMC Journal, 2023)
This paper seeks to explore meta-theatricality and self-reflexivity in Abhi Subedi’s two plays, A Journey into Thamel and The Caretaker’s Sky, to mark how the playwright reflects the changing social and cultural milieus of Nepal through these dramatic techniques. Through a close reading of Subedi’s A Journey into Thamel and The Caretaker’s Sky from the metatheatrical perspectives propounded by Lionel Abel and Richard Hornby, the research surveys how the playwright connects theatricality and realism in these plays. A Journey into Thamel portrays the hardships of people living in the post-war scenario of Nepalese society. The Caretaker’s Sky deals with the quest for freedom of creativity. But both plays share the common ground in terms of form, as Subedi’s dramaturgy expresses using metadrama as a rhetorical vehicle. In doing so, he uses as many metatheatrical tools as possible in making the plays self-reflective. The chief finding of this research is that Abhi Subedi exploits meta-drama as a rhetorical vehicle and at a time responds to the co-existence of realistic drama, staged theatricality, and anti-theatricalism in these plays so as to portray the Nepalese problems. The research scholars intended to work on Nepali theatre are expected to take the paper as a reference.